A Response Surface Methodology optimization approach to architect low-cost activated carbon-based ternary composite for supercapacitor application with enhanced electrochemical performance - Pandey V.K.; Verma S.; Verma B. (My University, 2025)
Nowadays, energy storage technologies have attracted much interest because there is a massive demand for electronic gadgets, electric automobiles, and automotive applications. Supercapacitors are gaining prominence as electrochemical energy storage applications because of their exceptional properties like fast charging, high power density, and outstanding cyclic stability. They are designed to fill the performance barrier between traditional capacitors and conventional batteries. This paper reports detailed optimization studies for low-cost ternary composite materials for supercapacitive applications with the help of Response Surface Methodology (RSM). The optimum composition was 4:1.03:2.66 (polyaniline: activated carbon: cobalt ferrite) for best electrochemical performance. The specific capacitance of the optimized composite material was 687.9 F/g. The optimized ternary composite material also demonstrated the 47.5 Wh/kg highest energy density and extraordinarily high capacitance retention of 76.1 % after completing 5000 cycles. © 2025 Elsevier B.V.